Phosphorus sorption and saturation in the Ganges tidal floodplain soils of Bangladesh - Hoque, Md. Fazlul; Or Rashid, Md. Harun; Islam, Md Rafiqul; Islam, Md. Saiful; Saleque, Md. Abu (Penerbit Universiti Kebangsaan Malaysia, 2018)
The soils developed from the Ganges sediments in the coastal area of Bangladesh and India extend several thousand hectares and important from the view point of rice cultivation. Phosphorus, one of the important environmental and agricultural element, retention behavior of the Ganges floodplain soils is poorly reported. The objective of this study was to determine maximum phosphorus adsorption capacity (MPAC) and to develop Psat for 13 Ganges Tidal Floodplain soils of Bangladesh. The MPAC value and Psat based on Mehlich-3 extractions were determined. The conventional adsorption equations, such as the Langmuir, Freudlich and Temkin equations were used to describe the P sorption of the studied soils. The MPAC value varied from 1250 to 2000 mg/kg and correlated with EC (r = 0.59, p<0.05) and CEC (r = -0.74, P<0.01). The sorption capacity of the tested soils ranged from 511 to 545 mg/kg and the calculated energy of adsorption of the soils varied from 0.192 to 1.00 μg/mL and it was a positively correlated with clay (r=0.7, p<0.01) and CEC (r = 0.63, p<0.05) but negatively with silt (r= -0.80, p<0.01), pH (H2O) (r=-0.60, p<0.05) and with MPAC (r=-0.59, p<0.05) values. Phosphorus saturation indices of the studied sample demonstrated a far below the threshold critical limit of 25%.